Retinal pathway origins of the pattern ERG of the mouse - Miura, Gen (2009)
This study investigated contributions from the retinal On and Off pathways, and the spiking and nonspiking activity of neurons in those pathways to the pattern ERG of the mouse. Light-adapted pattern and ganzfeld ERGs were recorded from anesthetized C57BL/6 mice 3-4 months of age. Recordings were made before and after intravitreal injections of PDA (cis-2, 3-piperidine-dicarboxylic acid) to block transmission to hyperpolarizing 2nd order and all 3rd order neurons, TTX (tetrodotoxin) to block Na(+)-dependent spiking, APB (2-amino-4-phosphonobutyric acid) to block synapses between photoreceptors and ON-bipolar cells, and APB+TTX and PDA+TTX cocktails. The pattern stimuli consisted of 0.05 cy/deg gratings reversing in contrast at 1 Hz, presented at various contrasts (50-90%) and a rod saturating mean luminance. For flash ERGs, brief green ganzfeld flashes were presented on a rod suppressing green background. Recordings were made 39-42 days after unilateral optic nerve crush (ONC) in a subset of animals in which ganglion cell degeneration was subsequently confirmed in retinal sections. Pattern ERGs were similar in waveform for all contrasts, with a positive wave (P1) peak for 90% contrast around 60 ms on average and maximum trough for a negative wave (N2) around 132 ms after each contrast reversal; amplitudes were greatest for 90% contrast which became the standard stimulus. ONC eliminated or nearly eliminated the pattern ERG but did not affect the major waves of the flash ERG. PDA and TTX both delayed P1 and N2 waves of the pattern ERG, and reduced their amplitudes, with effects of PDA on N2 greater than those of TTX. In the flash ERG, PDA reduced a-wave amplitudes, removed OPs but hardly affected b-wave amplitudes. In contrast, TTX reduced b-wave amplitudes substantially, as previously observed in rat. APB removed P1 of the pattern ERG, but left a negative wave of similar timing and amplitude to N2. In the flash ERG, APB removed the b-wave, producing a negative ERG. Addition of TTX to the APB injection removed most of N2 of the pattern ERG, while other waves of the pattern and flash ERG resembled those after APB alone. Addition of TTX to the PDA injection had little effect on the pattern ERG beyond that of PDA alone, but it prolonged the b-wave of the flash ERG. In conclusion, this study confirmed that a selective lesion of ganglion cells will practically eliminate the pattern ERG. The study also showed that P1 of the mouse pattern ERG is dominated by contributions, mainly spiking, from ON pathway neurons, whereas N2 reflects substantial spiking activity from the OFF pathway as well as non spiking contributions from both pathways.